Goods : Advertising, Urban Space, and the Moral Law of the Image - Coccia, Emanuele; Coccia, Emanuele (Book collections on Project MUSE., 2018)
In the advertising imaginary, to be human is to be a moral cyborgs whose existence attains ethical perfection only via the universe of things. The necessary alienation which commodities cause and express is moral rather than economic or social; we need our own products not just to survive biologically or to improve the physical conditions of our existence, but to live morally. Ultimately, Coccia's provocative book offers a radically political rethinking of the power of images. The problem of contemporary politics is not the anesthetization of words but the excess power we invest in them. Within images, we already live in another form of political life, which has very little to do with the one invented and formalized by the ancient and modern legal tradition. All we need to do is to recognize it. Advertising and fashion are just the primitive, sometimes grotesque, but ultimately irrepressible prefiguration of the new politics to come.